Concomitant developmental dental anomalies in Chinese children with dens evaginatus - S. Y. CHO, Y. KI, V. CHU & J. CHAN (Paediatric Dentistry, 2006)
To determine the prevalence of concomitant developmental dental anomalies in a group of Chinese children with dens evaginatus.